Conceptual Formulation for Crack Mapping Prediction Using Stochastic Modelling - Chuah, Pei Lim (2021)
Non-destructive testing (NDT) is an analysis method employed to assess material or structure properties without causing damage to the part. The Impactecho method is widely used in the construction field, featuring Rayleigh wave and pressure wave exploitation. Although the evaluation of concrete defection has been carried out using NDT, the crack mapping model is rarely used due to the infantile methodology. Hence, this study aims to develop an integrated three-dimensional crack mapping prediction model using stochastic processes. In this study, the elastic wave propagation in a concrete medium was replicated using the Delta method and ABAQUS simulation. The proposed crack mapping model included ellipse-based interpolation and beta reflection methods for surface and cross-section analysis. The surface crack mapping identifies the crack's location and provides variance of wave velocities (beta value). The cross-section analysis correlates to the beta value showing a three-dimensional crack mapping prediction model with corresponding depth. The simulation result from the crack mapping model agrees well with the theoretical sample with the slightest discrepancies. This finding also considered the heterogeneity properties of concrete, which exhibits the lognormal distribution of Young’s modulus and Poisson ratio. Both deterministic and stochastic results confirmed that the model has high reliability to detect the concrete flaw despite the random distribution of engineering properties. In a nutshell, the conception formulation for crack mapping predicting using stochastic modelling is developed with higher accuracy and the least iterations of NDT needed.